2009
DOI: 10.1016/j.mce.2008.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Functional interactions between 7TM receptors in the Renin-Angiotensin System—Dimerization or crosstalk?

Abstract: Abstract:The Renin-Angiotensin System (RAS) is important for the regulation of cardiovascular physiology, where it controls blood pressure, and salt-and water homeostasis. Dysregulation of RAS can lead to severe diseases including hypertension, diabetic nephropathy, and cardiac arrhythmia, and -failure.The importance of the RAS is clearly emphasised by the widespread use of drugs targeting this system in clinical practice. These include, renin inhibitors, angiotensin II receptor type I blockers, and inhibitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 117 publications
(199 reference statements)
2
35
0
Order By: Relevance
“…Homodimerization and heterodimerization in the AT1 and AT2 have been shown to modulate the effect of Ang II, perhaps in a tissue-specific manner [60,62]. We have observed a basal stimulation of 3 H-leucine incorporation of 18% by 10 lM AT1 antagonist losartan and a more profound stimulation of 32% by 10 lM AT2 antagonist PD123319.…”
Section: Nox and Myometrium Hypertrophy 309mentioning
confidence: 60%
See 1 more Smart Citation
“…Homodimerization and heterodimerization in the AT1 and AT2 have been shown to modulate the effect of Ang II, perhaps in a tissue-specific manner [60,62]. We have observed a basal stimulation of 3 H-leucine incorporation of 18% by 10 lM AT1 antagonist losartan and a more profound stimulation of 32% by 10 lM AT2 antagonist PD123319.…”
Section: Nox and Myometrium Hypertrophy 309mentioning
confidence: 60%
“…Formation of homo-or hetero-oligomers is commonly found among G protein-coupled receptors and has complicated our understanding of the signaling networks [60]. It has been found that AT1-mediated signaling was activated and enhanced by heterodimerization with the bradykinin B 2 receptor [61].…”
Section: Nox and Myometrium Hypertrophy 309mentioning
confidence: 99%
“…Furthermore, phosphorylation independent of G␣ q protein activation was also seen on three previously undiscovered FGF receptor phosphorylation sites. Ang II also resulted in phosphorylation of other 7TMRs including the ␤ 2 -adrenergic receptor, which is an AT 1 R interaction partner on a functional level (45).…”
Section: Fig 2 Distribution Of Phosphopeptidesmentioning
confidence: 99%
“…When Ang 1-7 and A779 were used at equimolar doses, Ang 1-7 antagonist failed to block Ang 1-7-induced depressor response against AT1R blockade; suggesting that Ang 1-7 may act via the AT2R (43). Therefore, there is a complex interaction between RAS receptors (4, 6), and some actions of Ang 1-7 may also be blocked by AT1R (1,5) or AT2R antagonists (9); suggesting a crosstalk between the MasR and Ang II receptors (20). Other data indicated that the antidiuretic effect of AVE0991 that mimics the effects of Ang 1-7 was completely blocked by PD123319 and partially blocked by losartan (43).…”
Section: Discussionmentioning
confidence: 99%
“…The role of Ang 1-7 in cardiovascular system has been studied; however, the exact mechanism is not completely understood (17). In addition, blockade of AT1R and AT2R also inhibits some actions of Ang 1-7, which indicates a crosstalk between MasR and Ang II receptors (4,6,20,45). Moreover, increase in nitric oxide (NO), bradykinin, and prostacyclin production complicates the mechanism of Ang 1-7 action (3).…”
mentioning
confidence: 99%